Exhumed : a history of zombies [videorecording (DVD)] - Zarka, Emily; Schulte, David (PBS, 2021)
Join Dr. Emily Zarka, who studies literature and film through the lens of monsters, as she deconstructs some of the most significant moments in zombie pop culture over the last 200 years to reveal what these creatures say about people. From our fears and conflicts to political uprisings, stories about zombies offer a way to better understand how ultimately, the monster feared the most is themselves.